2014
DOI: 10.1007/s40616-013-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Verbal Behavior Milestones Assessment and Placement Program (VB-MAPP): Teaching Assessment Techniques

Abstract: The Verbal Behavior Milestones Assessment and Placement Program (VB-MAPP) is an assessment tool used with individuals diagnosed with autism spectrum disorder and other language delays (Sundberg 2008). The milestones assessment section of the VB-MAPP is used to determine an individual's current skill level. The results of the milestones assessment can be used to identify instructional goals and objectives. The current study examined the effects of behavioral skills training (BST) on the administration of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 6 publications
1
11
0
4
Order By: Relevance
“…The research corroborated and extended what was produced in the literature, in the sense that the BST training resulted in increasing levels of performance accuracy for different populations (Sarakoff & Sturmey, 2004;Lerman et al, 2008;Lerman et al, 2013;Barnes, Mellor & Rehfeldt, 2014;Faggiani, 2014;Barboza et al, 2015;Lerman et al, 2015;Shireman, Lerman & Hillman, 2016;Ferreira, Silva & Barros, 2016;Barkaia, Stokes & Mikiashvili, 2017;Martone, 2017;Aureliano, 2018;Guimarães et al, 2018;Matos et al, 2019). It is important to consider that in the present research, none of the Psychology interns were familiar with ASD and Applied Behavior Analysis (ABA) to ASD, like the participants from the study conducted by Matos et al (2019).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The research corroborated and extended what was produced in the literature, in the sense that the BST training resulted in increasing levels of performance accuracy for different populations (Sarakoff & Sturmey, 2004;Lerman et al, 2008;Lerman et al, 2013;Barnes, Mellor & Rehfeldt, 2014;Faggiani, 2014;Barboza et al, 2015;Lerman et al, 2015;Shireman, Lerman & Hillman, 2016;Ferreira, Silva & Barros, 2016;Barkaia, Stokes & Mikiashvili, 2017;Martone, 2017;Aureliano, 2018;Guimarães et al, 2018;Matos et al, 2019). It is important to consider that in the present research, none of the Psychology interns were familiar with ASD and Applied Behavior Analysis (ABA) to ASD, like the participants from the study conducted by Matos et al (2019).…”
Section: Discussionsupporting
confidence: 81%
“…Sarakoff & Sturmey (2004) and Lerman et al (2008) successfully taught special education teachers to accurately implement the teaching of repertoires through DTT to children with ASD. Barnes, Mellor & Rehfeldt (2014) and Martone (2017) taughtpsychologists and educators to accurately conduct ABA assessments (Sundberg, 2008) to determine entry repertoires of children with ASD. Barkaia, Stokes & Mikiashvili (2017) successfully trained psychologists to accurately implement the teaching of verbal operants to children with ASD, considering that the training of the professionals was conducted through videoconferences (internet-based training).…”
Section: Introductionmentioning
confidence: 99%
“…Isso possibilita um diagnóstico e uma intervenção cada vez mais precoce, e, portanto, um prognóstico mais promissor (BIBBY et al, 2002;WERNER et al, 2005). A busca por qualificação profissional é importante para que estratégias sejam elaboradas e implementadas em cada fase do quadro clínico e de acordo com as particularidades de cada criança com TEA (BARNES et al, 2014;GADIA et al, 2004), para assim proporcionar um tratamento diário e sistemático que produza resultados que equilibrem os excessos e os déficits de repertórios comportamentais. Percebe-se ainda a importância do treinamento de cuidadores de indivíduos com TEA para o avanço na compreensão do que fazer e como fazer, e para o melhor convívio social destes indivíduos (BRASIL, 2013).…”
Section: Discussionunclassified
“…Before adopting any measurement tool for research or clinical purposes, it is necessary to examine its psychometric properties. Prior studies have indicated that clinicians can conduct the VB-MAPP with high fidelity if they receive sufficient training (Barnes, Mellor, & Rehfeldt, 2014), and presumably with high reliably. Preliminary data indicate that it has good to excellent milestones scoring reliability (Montallana, 2018), but to our knowledge there are no published peer-reviewed studies that have examined this.…”
Section: Discussionmentioning
confidence: 99%